Glaucoma in Dogs and Cats - Management with Cyclocryotherapy - Ghiggi E. (2023)
© 2023 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: The treatment of glaucoma often requires numerous therapeutic modalities to achieve the desired reduction in intraocular pressure (IOP). Cyclodestructive procedures or ciliary body destruction have been performed using techniques with considerable differences in efficacy and complication rates. Among these methods, cyclocryotherapy is non-invasive and simple for the management of uncontrolled glaucoma in dogs and cats. The objective of this case report is to describe the technique of carbon dioxide cyclocryotherapy to reduce intraocular pressure in dogs and cats with glaucoma. Cases: Nine canine patients and one cat with glaucoma were treated with cyclocryotherapy performed under general anaesthesia. Clinical signs patients included blepharospasm, ocular pain, episcleral congestion and ocular hypertension. The patients showed higher levels of IOP, higher than 30 mmHg. Surgical treatment with general anaesthesia was applied. The pre-anaesthesia protocol included acepromazine 0.05 mg/kg with methadone 0.2 mg/kg, followed by intravenous propofol and maintenance with isoflurane and oxygen. An ophthalmological cryocautery unit was used with carbon dioxide as the cryogenic agent and a retinal cryoprobe of 3.2 mm diameter tip for the procedure. The method used was a double cycle of freezing and thawing for 60 s in each site. The cryoprobe was centred approximately 5 mm posterior to the corneoscleral limbus over the ciliary body. The temperature of each cyclocryotherapy spot was between -60°C and -80°C and each site was maintained in place for 60 s; 4 to 6 spots of the double freeze-thaw cycle were made. This technique did not have any serious complications during or after the application of cryotherapy, but chemosis and hyperaemia of the bulbar conjunctiva developed. Subconjunctival anti-inflammatory steroids were injected to minimise swelling and patient discomfort. Satisfactory results were observed; in all cases, the intraocular pressure decreased, with the usual result being a cosmetic and painless eye. Discussion: Even with recent surgical and medical advances, pain and blindness are still common occurrences in glaucoma in human and veterinary practice. The cyclodestructive procedures included cyclodialysis, cyclodiathermy, cyclocryotherapy, and cyclophotocoagulation. The cryosurgery in veterinary ophthalmology has many indications for the treatment of ocular diseases and is effective at decreasing intraocular pressure in patients with persistent uncontrolled glaucoma. Cyclocryotherapy has been shown to reduce intraocular pressure in dogs, cats, rabbits and humans with normotensive and glaucomatous eyes. The application of a cryoprobe over the ciliary processes results in ablating ciliary tissue so that aqueous humour inflow is reduced to acceptable levels. In the clinical cases evaluated, there was a reduction in intraocular pressure reaching acceptable levels, with the usual result being cosmetic and painless eye. Medical therapy remains the predominant method for treating glaucoma in veterinary patients; therefore, cyclocryotherapy is an effective, simple way to lower IOP and is a reasonable treatment option for glaucoma management. Cyclocryotherapy has shown good results, with a low learning curve and it can also be repeated if necessary.